Rhoticity in Malaysian English / Kamalashne Jayapalan - Kamalashne , Jayapalan (2016)
This study seeks to examine rhoticity among Tamil speakers of Malaysian English. A variety of English is considered rhotic when an r in the spelling of the word is pronounced in word final environment before a pause (e.g. paper#) or before a consonant (e.g. card). This is also known as non-prevocalic /r/. However, in Standard Spoken British English this phenomenon does not occur. Malaysian English pronunciation is modelled after British English which is non-rhotic. However, recent studies have found instances of rhoticity among Malaysian speakers. This study examines if there is evidence of rhoticity among three groups of Malaysian Tamil speakers. This study set out to address following research questions: (1) To what extent is there evidence of rhoticity in the English produced by the speakers? (2) To what extent is there a relationship between the speakers’ language and educational background and the production of the non-prevocalic /r/?. A total of 15 female speakers, who were divided into a younger (13 to 19 years) and older group of speakers (50 to 70 years) participated in this study. Background information on the speakers’ language use as well as educational backgrounds were examined to determine if there is a link between these characteristics and their production of the non-prevocalic /r/. The attitudes of speakers towards Malaysian English and native varieties of English, namely British and Malaysian English was also be examined for the same reason. The speakers were recorded reading a list of words containing orthographic r in word final environment before a pause, and before a consonant. Informal interview session with the speakers were also recorded, and words with orthographic r in the same position were identified for analysis. Praat Version 5.3.82 was used to measure the values of the third formant (F3) of the vowels in both rhotic and non-rhotic tokens at their mid-point based on their spectrogram and auditory examination. The combination of both perceptual and acoustic findings shows that the realisation of coda /r/ was not persistent especially among the older group. However, there was a higher incidence of rhoticity among the younger Malaysian who spoke English as a first language, and more so among those who attended International schools.